No strong dependence of Lyman continuum leakage on physical properties of star-forming galaxies at ≲ z ≲ 3.5. Issue 1 (23rd December 2021) - Saxena, A; Pentericci, L; Ellis, R S; Guaita, L; Calabrò, A; Schaerer, D; Vanzella, E; Amorín, R; Bolzonella, M; Castellano, M; Fontanot, F; Hathi, N P; et al.
ABSTRACT: We present Lyman continuum (LyC) radiation escape fraction ( f esc ) measurements for 183 spectroscopically confirmed star-forming galaxies in the redshift range 3.11 < z < 3.53 in the Chandra Deep Field South. We use ground-based imaging to measure f esc, and use ground- and space-based photometry to derive galaxy physical properties using spectral energy distribution (SED) fitting. We additionally derive [O iii ]  +  H β equivalent widths (that fall in the observed K band) by including nebular emission in SED fitting. After removing foreground contaminants, we report the discovery of 11 new candidate LyC leakers at ≳ 2σ level, with f esc in the range 0.14−0.85. From non-detections, we place 1σ upper limits of f esc  <0.12, where the Lyman-break selected galaxies have f esc  <0.11 and 'blindly' discovered galaxies with no prior photometric selection have f esc  <0.13. We find a slightly higher 1σ limit of f esc  <0.20 from extreme emission line galaxies with rest-frame [O iii ]  +  H β equivalent widths >300 Å. For candidate LyC leakers, we find a weak negative correlation between f esc and galaxy stellar masses, no correlation between f esc and specific star-formation rates (sSFRs) and a positive correlation between f esc and EW0 ([O iii ]  +  H β). The weak/no correlations between stellar mass and sSFRs may be explained by misaligned viewing angles and/or non-coincident time-scales of starburst activity and periods of high f esc . Alternatively, escaping radiation may predominantly occur in highly localized star-forming regions, or f esc measurements may be impacted by stochasticity of the intervening neutral medium, obscuring any global trends with galaxy properties. These hypotheses have important consequences for models of reionization.